PENGARUH BRAND AWARENESS, BRAND AMBASSADOR DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE SHOPEE DI KOTA DENPASAR - I Gede Dika Wiguna; Ni Putu Nita Anggraini; I Wayan Gede Antok Setiawan Jodi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2023)
Abstract This study aims to explain the influence of brand awareness, brand ambassadors and electronic word of mouth on purchasing decisions at e-commerce Shopee in Denpasar City. The population in this study are people who have the Shopee application in Denpasar City. Sampling using a non-probability sampling method, namely a number of 100 respondents. The analysis technique used is multiple linear regression analysis. The results showed that brand awareness had a positive and significant effect on purchasing decisions, brand ambassadors had a positive and significant effect on purchasing decisions and electronic word of mouth had a positive and significant effect on purchasing decisions. Suggestions for further researchers can develop this research by adding other variables.